Mental fatigue and return to well-being in athletes: roles of cognitive reappraisal, gender, and alcohol consumption - Mehmet Kara; Emre Bulent Ogras; Laurentiu-Gabriel Talaghir; Teodora Mihaela Iconomescu; Huseyin Gumus (Frontiers in Psychology)
This study aimed to investigate the impact of mental fatigue awareness on psychological recovery processes in athletes. It also examines the mediating role of cognitive reappraisal and the moderating effects of gender and alcohol use. A sample of 639 active athletes from diverse regions of Turkey participated in the online study. Data were collected through the Sport Psychological Recovery Scale, the Emotion Regulation Scale for Athletes, and the Mental Fatigue Awareness Scale in Athletes. The findings indicate that mental fatigue awareness has a direct, negative effect on recovery (β = −0.2526, p < 0.001). Also, cognitive reappraisal partially mediates this relationship (β = −0.236, p < 0.001). Gender was identified as a significant moderator, with women exhibiting a stronger negative impact of mental fatigue awareness on their recovery processes compared to men. However, the moderating effect of alcohol consumption was not statistically significant. The study contributes to the understanding of the interplay between mental fatigue awareness and recovery in athletes, highlighting the influence of cognitive and emotional regulation and the importance of gender as a moderating variable. Future research should employ longitudinal designs and larger samples to explore these relationships in greater depth.